Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

Donner naissance: doulas, sages-femmes & justice reproductive - Apfel, Alana; Ross, Loretta J.; Law, Victoria; Federici, Silvia; Pruvost, Geneviève; Tincelin, Adel (Cambourakis, 2024)
Donner naissance . Doulas, sages-femmes & justice reproductive . Alana Apfel nous propose un recueil vivant de treize récits écrits par des doutas, des sages-femmes et des activistes féministes aux États-Unis qui racontent la naissance autrement. Au modèle de la toute-puissance médicale qui saurait mieux que les femmes elles-mêmes ce qu'est un « bon » accouchement est opposé ici un tout autre professionnalisme, à la fois discret et attentif, qui permet de faire une juste place à des femmes indignement traitées. Militer pour la « justice reproductive », c'est créer des « communs » de la naissance, selon la formule de Silvia Federici dans son introduction.. La postface de Geneviève Pruvost nous rappelle que l'obstétrique française est la plus médicalisée d'Europe. À l'heure où, en France, les sages-femmes à domicile font l'objet d'une tentative d'éradication professionnelle, Donner naissance nous propose une nouvelle manière de penser les trajectoires reproductives et nous fournit les outils théoriques et pratiques nécessaires
Section: 1 vol. (262 p.) : ill. ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; care; corps; cours; discipline; justice reproductive; justice sociale; maternité; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis